Relationship between Workload and Work Stress with Work Productivity in the Production Section of PT Andalas Dolomite Sejahtera Tanjung Lolo Sijunjung Year 2024 - Aprinda, Aprinda; Asmawati, Asmawati; Yanti, Meyi (STIKes Alifah Padang, 2024)
Work productivity is the comparison between output results and inputs that have been determined by the company. Work productivity is the main focus of the company at this time because the results of employee performance are still many have not met the production targets set by the company. This study aims to determine the relationship between workload and work stress with work productivity in the production section of PT Andalas Dolomite Sejahtera Tanjung Lolo Sijunjung in 2024. The research method used is quantitative method with cross sectional design. The research was conducted from March to August 2024. The population in this study were all employees of the production section, a sample of 60 respondents in the production section of PT Andalas Dolomite Sejahtera Tanjung Lolo Sijunjung Year 2024 with total population technique. Data were collected using questionnaires and interviews. Data analysis was carried out univariate and bivariate.The results of research on employees in the production section of PT Andalas Dolomite Sejahtera Tanjung Lolo Sijunjung in 2024 showed that more than half (60%) of respondents worked unproductively, and also more than half (58%) of respondents had a heavy workload and 52% of respondents had severe work stress. The research also showed that there was a relationship between workload and work productivity (p-value 0.000). And also found that there is no relationship between work stress and work productivity (p-value 0.349). From the research results, it was concluded that there is a relationship between workload and work productivity in production workers and there is no relationship between work stress and work productivity in production workers at PT Andalas Dolomite Sejahtera Tanjung Lolo Sijunjung in 2024. It is expected for the company to pay more attention to considerations in setting production targets set for production employees and also pay attention to the psychological health of employees.